Evaluation of the fidelity of an interactive face-to-face educational intervention to improve general practitioner management of back pain. Issue 7 (8th July 2015) - French, Simon D; Green, Sally E; Francis, Jill J; Buchbinder, Rachelle; O'Connor, Denise A; Grimshaw, Jeremy M; Michie, Susan
Abstract : Objectives: Implementation intervention effects can only be fully realised and understood if they are faithfully delivered. However the evaluation of implementation intervention fidelity is not commonly undertaken. The IMPLEMENT intervention was designed to improve the management of low back pain by general medical practitioners. It consisted of a two-session interactive workshop, including didactic presentations and small group discussions by trained facilitators. This study aimed to evaluate the fidelity of the IMPLEMENT intervention by assessing: (1) observed facilitator adherence to planned behaviour change techniques (BCTs); (2) comparison of observed and self-reported adherence to planned BCTs and (3) variation across different facilitators and different BCTs. Design: The study compared planned and actual, and observed versus self-assessed delivery of BCTs during the IMPLEMENT workshops. Method: Workshop sessions were audiorecorded and transcribed verbatim. Observed adherence of facilitators to the planned intervention was assessed by analysing the workshop transcripts in terms of BCTs delivered. Self-reported adherence was measured using a checklist completed at the end of each workshop session and was compared with the 'gold standard' of observed adherence using sensitivity and specificity analyses. Results: The overall observed adherence to planned BCTs was 79%, representing moderate-to-high intervention fidelity. There was no significant difference in adherence to BCTs between the facilitators. Sensitivity of self-reported adherence was 95% (95% CI 88 to 98) and specificity was 30% (95% CI 11 to 60). Conclusions: The findings suggest that the IMPLEMENT intervention was delivered with high levels of adherence to the planned intervention protocol. Trial registration number: The IMPLEMENT trial was registered in the Australian New Zealand Clinical Trials Registry, ACTRN012606000098538 (http://www.anzctr.org.au/trial_view.aspx?ID=1162 ).